El Salvador : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
This 2004 Article IV Consultation highlights that economic growth in El Salvador in recent years has been dampened by adverse external conditions, major earthquakes, and election-related uncertainties. Real GDP growth is estimated at about 1 1\2 percent in 2004 while inflation picked up to more than 5 percent, owing to higher oil prices. The public sector deficit is expected to decline to 3 percent of GDP in 2004. Executive Directors have praised El Salvador's long-standing record of structural reform and commitment to sound macroeconomic policies, and considered that official dollarization has served El Salvador well.